Long-term effects of grade retention - Meulen, Simon ter (CESifo, 2023)
Grade retention offers students a chance to catch up with unmastered material but also leads to less labor-market experience by delaying graduation and labor-market entry. This is the first paper to quantify this trade-off, using an exit exam cutoff of Dutch academic secondary schools, where failing implies grade retention. I find no impact of retaining on final educational attainment, although retained students are later to graduate. Grade retention does lead to annual earnings loss at age 28 of 3000 euro (8.5%) due to reduced labor-market experience. Overall, grade retention is of no benefit for students around the cutoff.
10419/271856
Keywords: Graue Literatur; grade retention; secondary education; higher education degrees; earnings loss